2017
DOI: 10.1128/aac.01090-17
|View full text |Cite
|
Sign up to set email alerts
|

Subinhibitory Dalbavancin Attenuates Exotoxin Production from Methicillin-Sensitive and Methicillin-Resistant Staphylococcus aureusIn Vitro

Abstract: This study investigated the effects of subinhibitory doses of the lipoglycopeptide antibiotic dalbavancin on toxin production toxin production levels were compared to those seen with the natural glycopeptide antibiotic vancomycin and with representative beta-lactam and oxazolidinone antibiotics. While neither dalbavancin nor vancomycin adversely affected toxin production, of these glycopeptide antibiotics, only dalbavancin significantly attenuated toxin production at subinhibitory concentrations. These finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In this sense, bacteria are frequently exposed to Sub-MIC of the antimicrobial agent and these conditions could result in mutagenesis and release of microbial virulence factors (Andersson and Hughes, 2014;Jo and Ahn, 2016;Larsen et al, 2016;Huijbers et al, 2019). Thus, it is important to evaluate the effects of the antimicrobial agents in pathways related to mutagenesis and virulence (Hobdey et al, 2017;Duan et al, 2018). We first showed that EbEO did not induce the expression of recA which is the first gene in the SOS response.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, bacteria are frequently exposed to Sub-MIC of the antimicrobial agent and these conditions could result in mutagenesis and release of microbial virulence factors (Andersson and Hughes, 2014;Jo and Ahn, 2016;Larsen et al, 2016;Huijbers et al, 2019). Thus, it is important to evaluate the effects of the antimicrobial agents in pathways related to mutagenesis and virulence (Hobdey et al, 2017;Duan et al, 2018). We first showed that EbEO did not induce the expression of recA which is the first gene in the SOS response.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of S. aureus optimal AUC24hr/MIC ratios for dalbavancin are predicted to be 100-300, much lower than the 400-600 target suggested for vancomycin [30,31]. Some in vitro data suggest that dalbavancin might possess other advantages over classical glycopeptides including greater potency against organisms in the bio lm state and the ability to suppress bacterial exotoxin production, though this has not been corroborated in clinical studies [32,33]. Dalbavancin is highly active against most clinically relevant Gram-positive organisms with the notable exception of vancomycin resistant enterococci, or more rarely vancomycin resistant Staphylococcus aureus (VRSA) carrying the vanA gene, as well as some species seldom encountered as pathogens such as Enterocloster clostridioformis [26,27,28].…”
Section: Introductionmentioning
confidence: 97%
“…In the case of Staphylococcus aureus, optimal AUC 24 h /MIC ratios for dalbavancin are predicted to be 100–300, much lower than the 400–600 target suggested for vancomycin [ 30 , 31 ]. Some in vitro data suggest that dalbavancin might possess other advantages over classical glycopeptides including greater potency against organisms in the biofilm state and the ability to suppress bacterial exotoxin production, though this has not been corroborated in clinical studies [ 32 , 33 ]. Dalbavancin is highly active against most clinically relevant Gram-positive organisms with the notable exception of vancomycin-resistant enterococci or more rarely vancomycin-resistant Staphylococcus aureus (VRSA) carrying the vanA gene, as well as some species seldom encountered as pathogens such as Enterocloster clostridioformis [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%